2005
DOI: 10.1079/bjn20041311
|View full text |Cite
|
Sign up to set email alerts
|

The influence of moderate red wine consumption on antioxidant status and indices of oxidative stress associated with CHD in healthy volunteers

Abstract: The effects of moderate red wine consumption on the antioxidant status and indices of lipid peroxidation and oxidative stress associated with CHD were investigated. A randomised, controlled study was performed with twenty free-living healthy volunteers. Subjects in the red wine group consumed 375 ml red wine daily for 2 weeks. We measured the total concentration of phenolics and analysed the individual phenolics in the wine and plasma by HPLC with tandem MS. The antioxidant capacity of plasma was measured with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
1
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(77 citation statements)
references
References 51 publications
1
71
1
4
Order By: Relevance
“…Plasma polyphenols increased after the intake of red wine, polyphenol-enriched white wine or red wine polyphenols (15,21,88) . Similarly, an increase was observed in the urinary excretion of 4-omethyl-gallic acid after the consumption of red wine and dealcoholised red wine (67) , in the urinary excretion of four metabolites from flavan-3-ols after the intake of red wine (77) and in the urinary excretion of resveratrol metabolites after the intake of red and white wine (17) .…”
Section: Measurement Of Antioxidant Compoundsmentioning
confidence: 96%
See 2 more Smart Citations
“…Plasma polyphenols increased after the intake of red wine, polyphenol-enriched white wine or red wine polyphenols (15,21,88) . Similarly, an increase was observed in the urinary excretion of 4-omethyl-gallic acid after the consumption of red wine and dealcoholised red wine (67) , in the urinary excretion of four metabolites from flavan-3-ols after the intake of red wine (77) and in the urinary excretion of resveratrol metabolites after the intake of red and white wine (17) .…”
Section: Measurement Of Antioxidant Compoundsmentioning
confidence: 96%
“…In the case of human subjects, although some studies reported no effect on plasma antioxidant capacity after supplementation with grape-derived products (98) , most of the trials did find some effect; for instance, increased plasma antioxidant capacity was observed after the intake of polyphenol extracts from red wine (32) , from grapes (33) , grape juice (65) , concentrated grape juice (80) , grape pomace (99) and red wine (77) . Also, studies on the possible effect of grape polyphenols in the postprandial phase have reported that after a meal accompanied by red wine, plasma antioxidant capacity by the total radical-trapping antioxidant parameter assay was sustained in type 2 diabetic subjects, whereas after the same meal without wine there was a significant decrease in antioxidant capacity (100) .…”
Section: Plasma Antioxidant Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…(+) Red wine increased plasma antioxidant capacity after 30 min to 3 hr Modun et al 2008 Daily consumption, less than four weeks (-) 200 mL red or white for 10 days had no effect on antioxidant status Sharpe et al 1995 (-) 375 mL red or white wine for 2 weeks did not reduce lipid peroxidation (in smokers) Abu-Amsha Caccetta et al 2001 (-) 4 glasses (600 mL b ) red wine for 3 weeks had no significant effect on overall antioxidant status (no washout period between wine, beer, spirit, and water conditions) van der Gaag et al 2000 (+) 200 mL red wine with three meals (meat soaked in red wine) prevented absorption of malondialdehyde, a cytotoxic lipid peroxidation product Gorelik et al 2008 (+) 250 mL red wine for 4 days decreased oxidized LDL levels and increased antioxidant enzyme activity Covas et al 2003 (+) 400 mL red wine for 2 weeks increased antioxidant status and decreased oxidative stress Micallef et al 2007 (+) 375 mL red wine daily for 2 weeks improved antioxidant status and indices of oxidative stress Tsang et al 2005 (+) 400 mL red (but not white) wine for 2 weeks reduced the susceptibility of human plasma and LDL to lipid peroxidation Fuhrman et al 1995 (+) 375 mL red wine for 2 weeks (or isolated red wine polyphenols dissolved in white wine) reduced LDL oxidation Nigdikar et al 1998 (+) Equivalent to 375 mL alcohol-free red wine extract for 2 weeks inhibited LDL oxidation Chopra et al 2000 (+) 375 mL red wine (or grape juice) for 2 weeks inhibited oxidation of LDL van Golde et al 1999 Daily consumption, four weeks or more (-) 1 glass red wine (or dealcoholized red wine) (150 mL b ) for 6 weeks did not increase plasma antioxidant capacity Arendt et al 2005 (-) 550 mL low-alcohol (3.5%) red or white wine for 4 weeks did not prevent LDL oxidation or change the level of antioxidants in the blood de Rijke et al 1996 (+) 250 mL red wine for 2 months reduced oxidative stress (acute coronary syndrome patients) Guarda et al 2005 (+) 240 mL red wine for 3 months increased plasma antioxidant capacity and decreased oxidative DNA damage Leighton et al 1999 (+) 375 mL white wine for 1 month increased the activity of antioxidant enzymes and decreased the activity of pro-oxidant enzymes Rajdl et al 2007 associated with a reduction in fibrinogen, plasma viscosity, and white blood cell count (Estruch et al 2004, Imhof et al 2004). In human and animal studies, grape juice and grape extract also supported immune function and exhibited antiinflammatory effects, supporting a role for wine polyphenols …”
Section: Finding Referencementioning
confidence: 99%
“…The Authors suggested that the inhibition of platelet reactivity by wine could have been one explanation for protection from coronary heart disease (CHV) in France people. In the attempt to verify the attractive relationship between antioxidant activity of red wine non-alcoholic components and platelet's responsiveness, a plethora of interesting studies were published, but the results remain even today discordant and far from being conclusive (De Lange et al 2003, Goldberg et al 2003, Gresele et al 2008, Tsang et al, 2005, Tozzi Ciancarelli et al 2011. Bioavailability of polyphenols is limited and their concentrations within the systemic circulation and tissues are very low in comparison with endogenous antioxidants, such as uric acid or ascorbic acid (Sies 2010, Hollman et al 2011, Ciancarelli et al 2015.…”
Section: The Mediterranean Diet: Current Concernsmentioning
confidence: 99%